MIXED PLEURAL MESOTHELIOMA WITH MYOCARDIAL METASTASIS IN BALB/C MOUSE - V. N. Manskikh; O. S. Gancharova (Сибирский онкологический журнал)
Mixed pleural mesothelioma is uncommon spontaneous tumor in laboratory mice. The case of this tumor in BALB/c mouse has been described in the paper. It is essential that myocardial metastasis has been observed. Differential diagnostics between pleural mesothelioma, pleural dissemination of bronchoalveolar adenocarcinoma and malignant thymoma has been discussed in relation to described tumor.